Fast and High‐Strain Electrochemically Driven Yarn Actuators in Twisted and Coiled Configurations. (16th December 2020) - Aziz, Shazed; Martinez, Jose G.; Salahuddin, Bidita; Persson, Nils‐Krister; Jager, Edwin W. H.
Abstract: Commercially available yarns are promising precursor for artificial muscles for smart fabric‐based textile wearables. Electrochemically driven conductive polymer (CP) coated yarns have already shown their potential to be used in smart fabrics. Unfortunately, the practical application of these yarns is still hindered due to their slow ion exchange properties and low strain. Here, a method is demonstrated to morph poly‐3, 4‐ethylenedioxythiophene:poly‐styrenesulfonate (PEDOT:PSS) coated multifilament textile yarns in highly twisted and coiled structures, providing > 1% linear actuation in < 1 s at a potential of + 0.6 V. A potential window of + 0.6 V and –1.2 V triggers the fully reversible actuation of a coiled yarn providing > 1.62% strain. Compared to the untwisted, regular yarns, the twisted and coiled yarns produce > 9×  and > 20×  higher strain, respectively. The strain and speed are significantly higher than the maximum reported results from other electrochemically operated CP yarns. The yarn's actuation is explained by reversible oxidation/reduction reactions occurring at CPs. However, the helical opening/closing of the twisted or coiled yarns due to the torsional yarn untwisting/retwisting assists the rapid and large linear actuation. These PEDOT:PSS coated yarn actuators are of great interest to drive smart textile exoskeletons. Abstract : A method of morphing conductive polymer coated textile yarns in twisted and coiled structures is demonstrated to achieve rapid and substantial linear actuation. The strain and speed are significantly higher than the maximum reported results from other electrochemically operated conductive polymer incorporated yarns. These yarn actuators are of great interest to drive smart textile fabrics and potentially results in low‐cost wearables.